Experimental Investigation on the Influence of Water Injection Timing on the Deformation of Loose Rock Blocks - Baoliang Zhang; Jian Li; Yongqiang Zhou; Yi Geng; Qingshuang Zhao; Dezhi Kong; Zihao Zhao; Changxiang Wang (Advances in Civil Engineering)
This study investigated the influence of water injection timing on the compression deformation of loose rock blocks in the goaf. The study used a confined gradient loading compression test to examine the deformation of loose rock blocks under initial saturation and later immersion conditions. The results showed that under initial saturation, the deformation of each loading gradient and the whole loading stage was greater than that of the later immersion stage. Additionally, the deformation of different stages in the initial saturated state was relatively regular, while in the later immersion state, the deformation changed abruptly after immersion. To explain the deformation mechanism of loose rock blocks, the mesostructure of loose rock blocks was granulated and the contact mechanism of particles was studied. The study found that water weakens the effective contact stress and strength between the skeleton particles, leading to sliding deformation as the dominant deformation mode. The study provides a theoretical basis for understanding the deformation characteristics of loose rock blocks in the goaf under different water environments.